Analisis Pengelolaan Dan Penyaluran Pendapatan Non Halal - Sri Wahyuningsih; Ari MH; Andi Suhandi; Azmy MH; De Euis Fitria (LPPM STEBIS YPII, 2024)
The purpose of this research is to find out what is the management of non-halal income and where is the allocation/distribution of non-halal income at Bank BJB Syariah KCP Lippo Cikarang, and to find out how Islam views non-halal income. This research is a descriptive type of research with a qualitative approach, which is sourced from primary data and secondary data that researchers collect through interviews, literature surveys and documentation. The results of this study are that Bank BJB Syariah KCP Lippo Cikarang recognizes fines as non-halal income, while for distribution, Bank BJB Syariah KCP Lippo Cikarang does not make this distribution but only manages its finances and then sends data to the center to compile its financial statements. Then the center will distribute the non-halal income to the previously reviewed institutions. The conclusion is that the practice of managing non-halal income is in accordance with sharia principles. In its distribution, Bank BJB Syariah KCP Lippo Cikarang does not make any distribution, but only manages its finances. In this case, there are some scholars who argue about non-halal income, namely some who argue that non-halal income can be used, and there are also scholars who argue that non-halal income is haram to be used.